2015
DOI: 10.1111/anae.12986
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of organ‐specific complications following abdominal aortic aneurysm repair using cardiopulmonary exercise testing

Abstract: SummaryThis study aimed at assessing whether measures of aerobic fitness can predict postoperative cardiac and pulmonary complications, 30-day mortality and length of hospital stay following elective abdominal aortic aneurysm repair. We prospectively collected cardiopulmonary exercise testing data over two years for 130 patients. Upon multivariate analysis, a decreased anaerobic threshold (OR (95% CI) 0.55 (0.37-0.84); p = 0.005) and open repair (OR (95% CI) 6.99 (1.56-31.48); p = 0.011) were associated with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 27 publications
(38 reference statements)
1
31
0
Order By: Relevance
“…18-21 Surgical procedures in which CPX has demonstrated prognostic value include abdominal aortic aneurysm repair, [22][23][24][25] radical cystectomy, 26 liver transplantation, 27 hepatic resection, 28 lung resection, [29][30][31][32][33] bariatric surgery, 34,35 and colorectal surgery. 36,37 In fact, the American College of Chest Physicians clinical practice guidelines for evaluation procedures of patients with lung cancer being considered for surgical resection recommend the use of CPX to assess risk.…”
Section: Cpx To Assess Perisurgical and Postsurgical Risk And Long-tementioning
confidence: 99%
“…18-21 Surgical procedures in which CPX has demonstrated prognostic value include abdominal aortic aneurysm repair, [22][23][24][25] radical cystectomy, 26 liver transplantation, 27 hepatic resection, 28 lung resection, [29][30][31][32][33] bariatric surgery, 34,35 and colorectal surgery. 36,37 In fact, the American College of Chest Physicians clinical practice guidelines for evaluation procedures of patients with lung cancer being considered for surgical resection recommend the use of CPX to assess risk.…”
Section: Cpx To Assess Perisurgical and Postsurgical Risk And Long-tementioning
confidence: 99%
“…Mortality at 30 or 90 days after either open AAA repair or EVAR was also associated with a low anaerobic threshold during preoperative CPET . Similarly, Barakat et al . carried out preoperative CPET assessments on patients before AAA repair (both open and EVAR) and demonstrated that a low anaerobic threshold was correlated with post‐operative cardiac complications.…”
Section: Discussionmentioning
confidence: 96%
“…Various risk factors based on past history, clinical examination and investigations, have been shown to correlate with postoperative outcome after surgery . Moreover, previous literature has demonstrated a relationship between cardiorespiratory capacity and postoperative complications as measured by cardiopulmonary exercise testing (CPET) , and the six‐minute walk test . Cardiopulmonary exercise testing measures have been shown to be able to distinguish those patients at risk of specific postoperative complications (i.e.…”
mentioning
confidence: 99%
“…Cardiopulmonary exercise testing measures have been shown to be able to distinguish those patients at risk of specific postoperative complications (i.e. cardiac or respiratory) . Barakat et al demonstrated that CPET‐derived measures of anaerobic threshold and ventilatory equivalents for CO 2 (trueV˙E/trueV˙CO 2 ) are predictive of postoperative cardiac and respiratory complications in vascular patients.…”
mentioning
confidence: 99%